Phenomenological Study on Workflow Efficiency and Response Time in Emergency Obstetric and Neonatal Care - Pratiwi Madya Putri Raden Roro; Guswan Wiwaha; Sri Wuryanti; Nurul Huda; Mia Mariani; Edy Prasetyo; Dicky Budiman (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Indonesia continues to face a high maternal mortality ratio, with delays in emergency obstetric care at referral hospitals remaining a critical contributor, despite the implementation of Comprehensive Emergency Obstetric and Neonatal Care (PONEK) services. These delays are frequently associated with inefficiencies in workflow and response time, particularly during post-triage management. This study aimed to explore healthcare workers’ lived experiences and to identify organizational, procedural, and systemic factors influencing workflow efficiency and response time in PONEK services at Y Hospital, Jakarta, a teaching hospital, referral center, and certified Syariah-based institution. A qualitative descriptive phenomenological design was employed, involving 15 purposively selected participants consisting of obstetricians, emergency physicians, midwives, nurses, administrative staff, and hospital managers directly engaged in PONEK services. Data were collected through in-depth interviews, non-participant observations, focus group discussions, and document review, and were analyzed using thematic analysis supported by content and SWOT analyses to ensure analytical rigor and triangulation. The findings revealed that while triage response time consistently met international standards of less than five minutes, significant delays occurred in subsequent stages of care due to fragmented inter-unit coordination, reliance on informal communication, inconsistent implementation of Standard Operating Procedures, and suboptimal utilization of the Hospital Management Information System (SIMRS). Additional barriers included incomplete referral documentation and the presence of non-emergency cases within the PONEK pathway, which disrupted prioritization and prolonged patient length of stay. In conclusion, workflow inefficiencies in PONEK services at Y Hospital are primarily driven by coordination gaps, human resource limitations, and insufficient digital integration rather than infrastructural shortcomings. Strengthening cross-unit collaboration, improving referral accuracy, enhancing staff capacity through continuous training, and optimizing digital systems are essential strategies to improve response time, service quality, and maternal emergency outcomes, thereby supporting hospital performance and contributing to the achievement of Sustainable Development Goal 3.1 on maternal mortality reduction.